Slaughter Quality of Broiler-Chickens by Prebiotic Actigen Using - Chernikova, Ganna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Biologically active agents were proposed like inciter of animals growing and alternative оf feed antibiotics and hormonal products. Prebiotic compounds are the most effective, because they have a positive effect on productivity, safety, immunity status, suppression of pathogenic microflora. Prebiotic doesn‘t have negative consequences. One of the most common prebiotic in Ukraine is Actigen. It is a highly purified, concentrate and specific controlled carbohydrate fraction, which was obtained from the cell wall of Saccharomyces cerevisiae. Actigen adding to broiler combined feed was learned in the poultry farm`s conditions. We learned product influence on slaughter quality of broilers. We recommended adding a preparation in large quantity based on the previous research of grain feed quality in the Ukrainian market. Company-developer proposed to use Actigen in quantity 400 g/T during all growing process. We proposed to use following quantity of Actigen in combine feed: starter – 800 g/T, growth 1–600 g/T, growth 2–400 g/T, finish 1–400 g/T, finish 2–300 g/T. According to the results of chicken broilers growing up to 42-day and holding a control, slaughter were receive increasing of preslaughter weight on 183.4 g, or 7.38% (P ≤0.05). Analysis of proceeding broiler chicken meat had shown the most changing of ratio different part the carcass. Received data showed that using of Actigen in proposed quantity for chicken broilers growing more expediency than recommended dosage.